Pengaruh Audit Tenure, Disclosure, Ukuran KAP, Debt Default, Opinion Shopping, Dan Kondisi Keuangan Terhadap Penerimaan Opini Audit Going Concern Pada Perusahaan Real Estate Dan Property Di Bursa Efek Indonesia - Ardiani, Nurul; DP, Emrinaldi Nur; Azlina, Nur (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2012)
The users of financial statements need informations as a basic of their economic decision making. Not only in judging the fairness of financial report or detecting a fraud, but also auditors have responsibility to judge the company ability to maintain company going concern. Going concern audit opinion defined as opinion state by the auditors based on their audit, concludes that substantial doubt exists with regard to the company’s ability to continue functioning as a business entity. In this study, we attempt empirically to investigate the relationship between Audit Tenure, Disclosure, KAP Size, Debt Default, Opinion Shopping and Financial Condition on receiving a going concern audit opinion of a company. The samples are selected by purposive sampling method. All real estate and property’s company listed in Indonesia stock Exchange that received going concern audit opinion from 2009-2011 are used as the population. Logistic Regression is used to test the hypothesis. From the results, indicate that Disclosure, KAP Size and Debt Default is significantly affect on receiving of going concern audit opinion. While the others (Audit Tenure, Opinion Shopping and Financial Condition), are not significantly affect on receiving of going concern audit opinion of a company.